Iodoacetic acid, but not sodium iodate, creates an inducible swine model of photoreceptor damage - Noel, Jennifer M. (2012)
Our purpose was to find a method to create a large animal model of inducible photoreceptor damage. To this end, we tested in domestic swine the efficacy of two chemical toxins, known to create photoreceptor damage in other species: Iodoacetic Acid (IAA) and Sodium Iodate (NaIO(3)). Intravenous (IV) administration of NaIO(3) up to 90 mg/kg had no effect on retinal function and 110 mg/kg was lethal. IV administration of IAA (5 – 20 mg/kg) produced concentration dependent changes in visual function as measured by full field and multi-focal electroretinograms (ffERG and mfERG), and 30 mg/kg IAA was lethal. The IAA-induced effects measured at two weeks were stable through eight weeks post-injection, the last time point investigated. IAA at 7.5, 10, and 12 mg/kg produce a concentration-dependent reduction in both ffERG b-wave and mfERG N1 – P1 amplitudes compared to baseline at all post-injection times. Comparisons of dark- and light-adapted ffERG b-wave amplitudes show a more significant loss of rod relative to cone function. The fundus of swine treated with ≥10 mg/kg IAA was abnormal with thinner retinal vessels and pale optic discs, and we found no evidence of bone spicule formation. Histological evaluations show concentration-dependent outer retinal damage that correlates with functional changes. We conclude that NaIO(3,) is not an effective toxin in swine. In contrast, IAA can be used to create a rapidly inducible, selective, stable and concentration-dependent model of photoreceptor damage in swine retina. Because of these attributes this large animal model of controlled photoreceptor damage should be useful in the investigation of treatments to replace damaged photoreceptors.